Size and trends of the bowhead whale, beluga and narwhal stocks wintering off West Greenland - Heide-Jørgensen, MP; Acquarone, Mario (NAMMCO Scientific Publications, 2002)
To assess the size and trends of the abundance of the bowhead whale (Balaena mysticetus), the beluga, or white whale (Delphinapterus leucas), and the narwhal (Monodon monoceros) visual aerial surveys were conducted in West Greenland in March 1998 and 1999. An estimated 49 bowhead whales (95% CI: 13 to 188) were present at the surface in 1998. Data from land-based observations enabled correction for bowhead whales that were not available at the surface to be seen during the survey. By applying a rounded average of 80% (SE=3) for submergence an estimate of 246 bowhead whales (95% CI: 62 to 978) in 1998 was obtained. The 76 and 47 sightings of beluga pods in 1998 and 1999, respectively, had distributions similar to those of previous surveys with the highest concentration at the northern edge of the northern part of Store Hellefiskebanke. No belugas were seen in the southernmost area between Maniitsoq and Paamiut. The index estimate of the abundance of belugas comparable with previous surveys was 929 (95% CI: 563 to 1,533) in 1998 and 735 (95% CI: 436 to 1,239) in 1999. When analysing the sightings as a line-transect survey and correcting for whales that were either submerged or at the surface but missed by the observers an estimated 7,941 (95% CI: 3,650 to 17,278) belugas wintered in West Greenland in 1998-1999. The uncorrected estimate of narwhal abundance was 524 (95% CI: 214 to 1,284) and correcting for the same biases as for the belugas gives a total abundance of 2,861 (95% CI: 954 to 8,578) narwhals in 1998-1999.